2021
DOI: 10.3389/fimmu.2020.620891
|View full text |Cite
|
Sign up to set email alerts
|

Co-Reactivation of Cytomegalovirus and Epstein-Barr Virus Was Associated With Poor Prognosis After Allogeneic Stem Cell Transplantation

Abstract: Reactivation of cytomegalovirus (CMV) or Epstein-Barr virus (EBV) is common after hematopoietic stem cell transplantation (HSCT). Previous researches have demonstrated that either CMV or EBV reactivation is associated with poor outcomes of HSCT. However, few studies investigate the impact of CMV and EBV co-reactivation after HSCT. In this study, we described the clinical characteristics of HSCT recipients with CMV and EBV co-reactivation (defined as CMV and EBV viremia occur at the same period of time). We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 21 publications
3
19
0
1
Order By: Relevance
“…CD28-mediated costimulation was very important in T-cell activation; CD4 + CD28 + T cells and CD8 + CD28 + T cells mediated graft-versus-leukemia (GVL) effect to prevent relapse, and CD4 + CD28 + T cells also mediated protection against infections ( 49 , 50 ). Poor CD4 + CD25 + T cell reconstitution increased the risk of infections ( 51 ). We observed that patients who recovered from SR-aGVHD after basiliximab treatment had a slower CD4 + CD25 + T-cell recovery compared with event-free HID HSCT recipients, which was supported by previous studies ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…CD28-mediated costimulation was very important in T-cell activation; CD4 + CD28 + T cells and CD8 + CD28 + T cells mediated graft-versus-leukemia (GVL) effect to prevent relapse, and CD4 + CD28 + T cells also mediated protection against infections ( 49 , 50 ). Poor CD4 + CD25 + T cell reconstitution increased the risk of infections ( 51 ). We observed that patients who recovered from SR-aGVHD after basiliximab treatment had a slower CD4 + CD25 + T-cell recovery compared with event-free HID HSCT recipients, which was supported by previous studies ( 52 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies consistently identified immunosuppression as the primary risk for multivirus infections (Table 1) [24,41,43]. Risk factors such as D/R HLA mismatch, unrelated donors, severe acute GVHD, myeloablative conditioning, lymphopenia, and use of lymphocyte-depleting agents were identified [22 ▪▪ ,46 ▪▪ ,47]. Of recipient factors, CMV seropositivity and increased age were also found to be associated with multiviral infections [22 ▪▪ ,44].…”
Section: Allogeneic Stem Cell Transplantsmentioning
confidence: 99%
“…CMV and Epstein-Barr virus reactivation are independent risk factors for sPGF within the first 100 days of allo-HSCT ( 4 , 88 ). CMV and Epstein-Barr virus co-reactivation not only leads to a shorter 1-year OS and leukemia-free survival, but also results in poor regulatory T cell reconstitution at day 30 after allo-HSCT ( 89 ). CMV reactivation (CMVR) after HSCT can lead to a variety of common life-threatening infectious complications such as pneumonia, retinitis, or sPGF.…”
Section: The Soilmentioning
confidence: 99%